Book reviews: Popescu Constantin – Life like tragic optimism – an ecolonomic perspective - Şimon, Ilie (Annals of Spiru Haret University. Economic Series, 2011)
As the title indicates, this is a book about life and its optimism, considered somehow tragic by an economist, who has been concerned for years with the balanced economic growth, based on production functions, rigorous from a mathematic point of view, and has done it successfully.